Perancangan Sistem Pencatatan Akuntansi Berbasis Perangkat Lunak Microsoft Access Pada Pt Batam Bordir Jaya - Muhammad Taufik; Jonathan Jonathan (Universitas Internasional Batam, 2021)
This community service aims to solve the problem of semi-manual accounting bookkeeping used by PT Batam Embroidery Jaya. Semi-manual accounting books cause financial statements to be irrelevant and do not meet the criteria of faithful representation. We collected data through in-depth interviews with business owners and field observations. The data obtained becomes an accounting bookkeeping simulation laboratory using Microsoft Access. The accounting bookkeeping system produces two outputs, namely accounting administration outputs and report. Bookkeeping administration outputs include a list of accounts, a list of suppliers, a list of supplies, a general journal form, purchase form, general journal form, a purchase form, a sales form, an inventory adjustment form, and a payable payment form. In addition, the report output includes income statement, balance sheet, sales report, purchase report, statement of changes equity, and inventory report. Both accounting administration outputs and reports are interconnected and become a relational database. Thus, the implementation of this system that is designed has positive implications for the company, namely that transactions are recorded to be more efficient and systematic. The report output generated by the system helps the person in charge of the company in making the right decisions for the company's future development.